PENGARUH FAKTOR-FAKTOR KOMPETENSI TERHADAP KINERJA KARYAWAN PADA CV. NUSANTRA PERS KABUPATEN KEPULAUAN ARU - Paais, Maartje (2019)
This study aims to analyze the effect of competency factors (knowledge, skills and personal characteristics) on employee performance on the CV. Nusantara Press Aru Islands Regency; and analyze the dominant influence between the competency factor variables (knowledge, skills and personal characteristics) on employee performance on the CV. Archipelago Press Aru Islands Regency. The study population was all employees in the CV. Archipelago Press Aru Islands Regency totaling 60 people. The sampling method uses a census sampling technique, so that in this study the sample was 60 employees at CV Nusantara Press Aru Islands Regency. The results showed that simultaneously variables of competency factors (knowledge, skills and personal characteristics) significantly influence employee performance on the CV. Nusantara Press Regency Aru Islands; while partially shows that the knowledge factor variable gives the most dominant influence on employee performance on the CV. Nusantara Press Regency Aru Islands